The Effect of Logical Choice Weight and Corrected Scoring Methods on Multiple Choice Agricultural Science Test Scores - Ajayi , B. K (Asian Journal of Agriculture and Rural Development, 2012)
The study focused on the effect of logical choice weight and corrected scoring methods on multiple choice Agricultural science test scores the study also investigated the interaction effect of logical choice weight and corrected scoring methods in schools ,and types of school in multiple choice agricultural science test. The researcher used a combination of survey type and one short experimental design. The sample for the study consisted of 600 students selected by stratified random sampling techniques in south western Nigeria. Overall performance of students in percentage, and correlation was analyzed. The hypotheses were generated and tested at 0.05 level of significance. The study revealed that there was a significant difference in the academic performance of students in logical choice weight and corrected scoring methods in multiple choice agricultural science test scores. The result also shown that there was no interaction effect on the two scoring methods in the type of schools, the location of schools in multiple choices agricultural science test. The study revealed that logical choice weight scoring method was the best method that favoured the scoring of the students’ scripts in multiple choices agricultural science test. On the basis of these findings, logical choice weight should be introduced to the teachers to use in the classroom as a new method of scoring multiple choice agricultural science the logical choice weight method is recommended in the ministry of education, in Examination Division, and to junior secondary schools for scoring JSS (3) three multiple choice test. Examination bodies such as West Africa Examination Council (WAEC), National Examination Council (NECO), Joint Admission and Matriculation Board (JAMB) should adopt the use of logical choice weight method in scoring multiple choice tests. The method could be used in tertiary institutions for post ‘JAMB’ Unify Matriculation Examination (UME) test. It is also recommended for all states of the federation as well the West African countries public service could also adopt the use of logical choice weight scoring method.